Arthropods Diversity and Population Dynamic of Helopeltis antonii Sign. (Hemiptera: Miridae) on Various Cocoa Agroecosystems Management - Mochamad Syarief; Gatot Mudjiono; A. Latief Abadi; Toto Himawan (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
As an important pest, Helopeltis Antonii reduces cocoa yields ca. 32-44 %. Related to H. antonii, this research aimed to identify the arthropods diversity, population and attack intensity of H. antonii in three different managements of cocoa plantations i.e. Kedaton, Banjarsari and Nogosari, Jember district, East Java, Indonesia from February 2014 to February 2015. The arthropod collection was done by visually, sweep net, yellow pan, malaise and pitfall traps. Arthropods diversity and similarity were analyzed by Margalef species richness index (R), Shannon-Wiener diversity index (H’), Evenness index (E), Simpson dominance index (C) and Sorensen Similarity index (SS). The different number of arthropod, population and attack intensity of H. antonii between plantations were examined by Wilcoxon test. The research showed that the highest species richness, diversity and evenness index values was in Nogosari and it was in a stable condition. About 10 orders, 35 families and 41 species of arthropods in Nogosari, it was higher than two other cocoa plantations. Nogosari was different from Kedaton and Banjarsari based on Sorensen Similarity Index with 78.26 and 77.78 % respectively. In addition, population dynamic and attack intensity of H. antonii in the three cocoa plantations were different in a year.